2022
DOI: 10.1186/s12951-022-01416-7
|View full text |Cite
|
Sign up to set email alerts
|

All-in-one approaches for triple-negative breast cancer therapy: metal-phenolic nanoplatform for MR imaging-guided combinational therapy

Abstract: Background Conventional chemotherapy has poor efficacy in triple-negative breast cancer (TNBC) which is highly heterogeneous and aggressive. Imaging-guided therapy is usually combined with diverse treatment modalities, could realize the integration of diagnosis and treatments. Therefore, the primary challenge for combinational therapy is designing proper delivery systems to accomplish multiple synergistic effects. Results Herein, a facile nanoplatf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…The all‐in‐one, theranostic formulation approach is the new trend that can combine almost all the theranostic‐based treatment approaches with chemotherapy and perform tumor microenvironment modulation with simultaneous imaging while in action (Xie et al, 2022). Zhao et al have developed a doxorubicin‐loaded, manganese dioxide conjugated, mesoporous silica‐coated bismuth nanoparticles (NPs) composites that show chemotherapy‐based tumor killing by doxorubicin, PTT‐based killing by bismuth NPs, and CDT based tumor removal by the MNO 2 present in the formulation.…”
Section: Nanomedicine‐based Approach To Treat Breast Cancer Resistancementioning
confidence: 99%
“…The all‐in‐one, theranostic formulation approach is the new trend that can combine almost all the theranostic‐based treatment approaches with chemotherapy and perform tumor microenvironment modulation with simultaneous imaging while in action (Xie et al, 2022). Zhao et al have developed a doxorubicin‐loaded, manganese dioxide conjugated, mesoporous silica‐coated bismuth nanoparticles (NPs) composites that show chemotherapy‐based tumor killing by doxorubicin, PTT‐based killing by bismuth NPs, and CDT based tumor removal by the MNO 2 present in the formulation.…”
Section: Nanomedicine‐based Approach To Treat Breast Cancer Resistancementioning
confidence: 99%
“…However, the efficacy of single therapy remains limited, thus necessitating the use of various methods in combination to enhance the efficiency and effectiveness of tumor treatment and improve the cure rate of cancer. [ 100 ] Currently, chemotherapy and CDT are the primary treatment methods, and PDT, acoustic dynamics, IIT, and other auxiliary treatments have been used in combination therapy. Combination therapy, which combines two or more treatments, has garnered increasing attention due to its superior efficacy to monotherapy.…”
Section: Combination Therapymentioning
confidence: 99%
“…Chemodynamic therapy (CDT) is an emerging therapeutic options that utilizes a Fenton-like reaction to kill tumor cells through endogenous production of reactive oxygen species (ROS) in the TME. An increased production of ROS not only destroys mitochondria and nuclei but also activates apoptotic pathways in tumor cells . In addition, studies have also shown that CDT combined with other treatments such as photothermal therapy (PTT) can significantly improve the effect and sensitivity of tumor treatment. PTT can also directly kill tumor cells by increasing the temperature of the tumor site, promote the release of tumor-associated antigens from the tumor in situ, and activate the immune response. Platinum nanoparticles (PtNPs) and gold nanoparticles (AuNPs) are reported to be nanoparticles with excellent properties and are widely used in mediating CDT and PTT. Hence, it is essential to construct a co-delivery system containing nanoenzymes and immune adjuvants to combine CDT, PTT, and immunotherapy to exert antitumor effects. , Together with the yeast microcapsules described above, this encourages the innovative modification of formulations from a microbial perspective by means of biosynthesis. , …”
Section: Introductionmentioning
confidence: 99%